Gas exchange in Annona emarginata (schltdl.) h. Rainer subjected to salt stress and application of plant growth regulator - Dalanhol, Samanta Jaqueline; Mantoan, Luís Paulo Benetti; Amaro, Amanda Cristina Esteves; Ferreira, Gisela (Scientia Agraria Paranaensis, 2018)
The aim of this study was to evaluate the effects of the application of plant growth regulator on gas exchange in A. emarginata seedlings subjected to different NaCl concentrations. We evaluated the gas exchange in A. emarginata seedlings subject to the presence and absence of plant growth regulator consisting of kinetin, gibberellic acid, and indolbutyric acid and three concentrations of NaCl (0 mM, 50 mM, and 100 mM). When assessing these factors individually, it was observed that in the presence of plant growth regulators, there was a reduction in stomatal conductance and transpiration, and NaCl concentration (50 mM and 100 mM) caused a reduction in CO2 assimilation, stomatal conductance, and transpiration. There was no significant interaction between plant growth regulators and salt stress. Therefore, gas exchange in A. emarginata seedlings when under salt stress is not influenced by the prior application of plant growth regulators. However, individually, both the implementation of the regulators and the salt stress led to a reduction of gas exchange in A. emarginata seedlings.